2014
DOI: 10.17796/jcpd.39.1.b45805v0v17407gl
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Release from Fluoride Varnishes under Acidic Conditions

Abstract: Objective: The aim was to investigate the in vitro fluoride release from fluoride varnishes under acidic conditions. Study design: Poly(methyl methacrylate) blocks (Perspex, n=3 per group) were painted with 80±5 mg fluoride varnish (n=10) and placed into artificial saliva for 30min. Then, blocks were placed into either 1% citric acid (pH 2.27) or 0.3% citric acid (pH 3.75) solutions (n=3 per solution and varnish) for 30min with the solutions being replaced every 5min. Saliva and acid solutions were analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Lippert observed that fluoride release from some fluoride varnishes varied considerably, and it was dependent on the pH of the dissolution medium. 23 Fluoride varnishes CavityShield, Nupro ® , ProFluorid ® and Vanish ® showed higher fluoride release to saliva than during the first 5 min of acid exposure, whereas other varnishes (Acclean ® , Enamel-Pro ® , MI Varnish, Vella ® ) revealed the opposite behavior. Our data also showed that the acidity of artificial saliva was associated with levels of fluoride release.…”
Section: Discussionmentioning
confidence: 86%
“…Lippert observed that fluoride release from some fluoride varnishes varied considerably, and it was dependent on the pH of the dissolution medium. 23 Fluoride varnishes CavityShield, Nupro ® , ProFluorid ® and Vanish ® showed higher fluoride release to saliva than during the first 5 min of acid exposure, whereas other varnishes (Acclean ® , Enamel-Pro ® , MI Varnish, Vella ® ) revealed the opposite behavior. Our data also showed that the acidity of artificial saliva was associated with levels of fluoride release.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, the varnishes were applied once and removed after 6 h of application to simulate the clinical condition, since the emphasis was allowing the chemical effect of the varnish components, rather than the mechanical protection. Because of their common clinical use, high fluoride amount and slow components release, varnishes could be an ideal product to be used as a preventive product against dental erosion (21).…”
Section: Discussionmentioning
confidence: 99%
“…As tooth structure experiences fluoride reservoir dissolution with drops in pH, fluoride varnish performance at different pH may be of interest [12]. There are studies to indicate that some fluoride-containing products show an increase in release with a decrease in pH while others show a decrease in release with a decrease in pH [32,33]. Intuitively, a topical fluoride varnish with high initial fluoride release would allow for greater amounts of fluoride available for enamel uptake [30]; however, some studies have shown fluoride efficacy cannot be measured by the product's fluoride release rate [34].…”
Section: Discussionmentioning
confidence: 99%